THE CONNECTION BETWEEN ORAL-GUT AXIS AND PEDIATRIC INFLAMMATORY BOWEL DISEASE - Otilia Iftinchi; Laura Otilia Boca; Lorena Mihaela Manole; Lorenza Forna; Gabriela Ghica; Gabriela Păduraru; Laura Mihaela Trandafir (Romanian Society of Oral Rehabilitation, 2023)
The oral microbiome, a diverse assembly of over 700 species, significantly influences human health, developing early in life and shaped by factors such as delivery mode and diet. This study explores the intricate interplay between the oral and gut microbiota, focusing on its relevance in pediatric inflammatory bowel disease (IBD). Notably, the research reveals distinct dysbiosis within the oral microbiome of children affected by IBD, suggesting these microbial changes as potential diagnostic markers. The study also investigates shifts in the oral microbiota before and after the initiation of IBD treatment. This multifaceted perspective underscores the relevance of oral health in the broader landscape of pediatric IBD management.